Unmasking the Mechanism behind Miltefosine: Revealing the Disruption of Intracellular Ca2+ Homeostasis as a Rational Therapeutic Target in Leishmaniasis and Chagas Disease - Gustavo Benaím; Alberto Paniz‐Mondolfi (2024)
Originally developed as a chemotherapeutic agent, miltefosine (hexadecylphosphocholine) is an inhibitor of phosphatidylcholine synthesis with proven antiparasitic effects. It is the only oral drug approved for the treatment of Leishmaniasis and American Trypanosomiasis (Chagas disease). Although its precise mechanisms are not yet fully understood, miltefosine exhibits broad-spectrum anti-parasitic effects primarily by disrupting the intracellular Ca